2019
DOI: 10.1113/ep087515
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of N‐acetyl‐seryl‐aspartyl‐lysyl‐proline with the angiotensin‐converting enzyme 2–angiotensin‐(1–7)–Mas axis attenuates pulmonary fibrosis in silicotic rats

Abstract: New Findings What is the central question of this study?What are the effects of the antifibrotic peptide acetyl‐seryl‐aspartyl‐lysyl‐proline (Ac‐SDKP) on the angiotensin‐converting enzyme 2 (ACE2)–angiotensin‐(1–7)–Mas axis during the occurrence and progression of silicosis? What is the main finding and its importance?Ac‐SDKP inhibited lung fibrosis in rats exposed to silica by activation of the ACE2–angiotensin‐(1–7)–Mas axis. Angiotensin‐(1–7) potentially promotes Ac‐SDKP by increasing the level of meprin α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Immunostaining for α-smooth muscle actin (α-SMA, EPR5368; Epitomics, Burlingame, CA, USA) was performed on lung sections as described previously. 8,9 Brown staining indicated samples positive for α-SMA expression.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Immunostaining for α-smooth muscle actin (α-SMA, EPR5368; Epitomics, Burlingame, CA, USA) was performed on lung sections as described previously. 8,9 Brown staining indicated samples positive for α-SMA expression.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…7 Our recent studies also showed that Ac-SDKP (N-acetyl-seryl-aspartyl -lysyl-proline) exerts an anti-silicotic effect through activation of the ACE2-Ang-(1-7)-Mas axis. 8,9 Our previous study found that the expression of ACE, Ang II and AT1 increased while that of ACE2 decreased in local lung tissue in mice with acute lung injury induced by limb ischemia-reperfusion. After preventive intervention with DIZE for 4 weeks, the lesions of the lung injury were attenuated, and the production of Ang-(1-7) and Mas receptor protein were up-regulated in the lung, whereas the opposite trend was observed for Ang II and the AT1 receptor protein.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…69 The structure of the S protein consists of four parts: an SP located at the N terminus (amino acids 1-12), an extracellular domain (amino acids 13-1195), a TM domain (amino acids 1196-1215), and an intracellular domain (amino acids 1216-1255). 16 The S1 subunit contains two independent domains, an N-terminal domain (NTD, amino acids 18-353) 70 and a C-terminal domain (amino acids 367-588), both of which may function as receptor-binding domains (RBDs); 71 these domains serve as critical targets for the development of vaccines and therapeutics 72,73 and facilitate the involvement of the S1 subunit in cell receptor (DPP4) binding. The core structure of the MERS-CoV S protein RBD is a five-stranded antiparallel sheet with several short helices, in which three disulfide bonds stabilize the core by connecting C383 to C407, C425 to C478, and C437 to C585.…”
Section: Epidemiological Analysis and Symptoms Of Sars Mers And Cormentioning
confidence: 99%
“…ARDS and acute lung injury are associated with damaged pulmonary microvascular endothelial cells (PMVECs), which result in increased alveolar permeability and pulmonary oedema ( Su et al, 2004 ). The balance between the expression of ACE1 and ACE2 is closely related to the ratio of Ang Ⅱ:Ang1-7, and an imbalance of Ang Ⅱ:Ang1-7 can lead to acute lung injury ( Gao et al, 2019 , Queiroz-Junior et al, 2019 , Wang et al, 2018 ).…”
Section: Vitamin D and Acute Lung Injurymentioning
confidence: 99%